Inclusive Education Management of Children with Special Needs In The Learning Process and Teacher Handling - Larosa, Yasozatulo; Zebua, Peringatan; Zebua, Yaarodotonafo; Heryanto, Heryanto (Green Publisher Indonesia, 2022)
One of the educational programs implemented to overcome the issue of discrimination in the field of education is inclusive education. The teacher is one of the important figures in the practice of inclusion in school institutions, because the teacher interacts directly with students, both students with special needs and non-special needs students. This study uses a descriptive qualitative research approach. In this study the researchers wanted to describe the management of the implementation of inclusive education in the learning process and the teacher’s handling of children with special needs (ABK). The research data was obtained through interviews, observation and documentation. Based on the description of the results of the research and discussion that has been carried out by researchers related to the management of inclusive education in the learning process and the handling of teachers for children with special needs, they must carry out management functions related to planning, organizing, activating, coordinating, directing and supervising starting from the process of learning strategies, learning media , teacher attitudes and evaluation of learning outcomes Suggestions for inclusive education programs to become school programs that can be implemented to avoid discrimination against all students in education